G-D’s Physics’ New “Geulah-Driven, Human Consciousness Focus” (GDHCF) Model of the Universe! - Bentovish, Jehonathan (European Journal of Applied Sciences, 2023)
Twentieth century's Old "Material-Causal" Paradigm underlying both General Relativity Theory (GRT) and Quantum Mechanics (QM) has reached a state of a "Paradigmatic-Crisis" signified by the apparent "theoretical inconsistency" between GRT & QM as well as its principle inability to account for up to 90% of all the mass and energy in the universe, e.g., assumed to comprise purely hypothetical "dark-matter" and "dark-energy" concepts and explain the universe's accelerated rate of expansion – but which could not be detected empirically (for the two past decades)?” A New promising “G-D’s Physics” (“Computational Unified Field Theory”, CUFT) “A-Causal Computation” Paradigm has been discovered based on the discovery of a singular higher-ordered “Universal Computational Principle” (UCP) that simultaneously computes all exhaustive spatial pixels in the universe at the incredible rate of “c2/h” = 1.36-50 (sec’) which produces an extremely rapid series of “Universal Frames (UF’s) comprising the entire physical universe at every “minimal time-point”! The New “G-D’s Physics” Scientific Paradigm is empirically validated in this article as more valid than the Old “Material-Causal” Paradigm based on verification of two unique “G-D’s Physics’ “Critical Predictions”: a) Universe’s Non-Continuous Increase in its Accelerated Rate of Expansion (UNCIARE); b) “Proton-Radius Puzzle” findings supporting “G-D’s Physics” UCP’s computation of relatively “more massive” particles (such as the Muon) as more “spatially-consistent” than relatively “less-massive” particles (such as the electron). Based on these empirical validations the New “G-D’s Physics” Paradigm negates the Old “Material-Causal” Paradigm’s GRT’s “Big-Bang” Model and offers an alternative (novel) “G-D’s Physics’ ‘Geulah-Driven’, Human Consciousness Focus (GDHCF) Model of the Universe’s origination, sustenance and development of the entire physical universe towards the UCP’s Ultimate “Geulah Perfected Goal State” of the universe in which Humanity (and Science) recognize the singularity of this UCP and its associated characteristics of “Morality”, “All-Goodness” “Peace” and “Harmony”!